2014
DOI: 10.5216/ree.v16i2.23611
|View full text |Cite
|
Sign up to set email alerts
|

Conhecimento e atitudes de profissionais de saúde sobre avaliação e manejo da dor neonatal

Abstract: Conhecimento e atitudes de profissionais de saúde sobre avaliação e manejo da dor neonatal Knowledge and attitudes of health professionals regarding pain assessment and management in neonatesConocimiento y actitudes de profesionales de salud sobre evaluación y manejo del dolor neonatal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0
25

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(69 citation statements)
references
References 19 publications
5
39
0
25
Order By: Relevance
“…A similar result was found by studies on perceptions, knowledge and practices of health professionals on the management of neonatal pain (9,(13)(14) . However, in this study we observed professionals who disagreed about the newborn's ability to feel pain.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…A similar result was found by studies on perceptions, knowledge and practices of health professionals on the management of neonatal pain (9,(13)(14) . However, in this study we observed professionals who disagreed about the newborn's ability to feel pain.…”
Section: Discussionsupporting
confidence: 85%
“…Pharmacological measures reported by nurses for pain relief of newborns were Paracetamol -24 (47.1%), Fentanyl -34 (47.1%), and Morphine -9 (17.6%). Other studies also mention these drugs in the treating of neonatal pain (9,14,18) . In this study, 38 (74.5%) of the nurses disagreed regarding the claim that newborns do not need analgesics due to the immaturity of their nervous system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Estudos científicos nacionais e internacionais apontam que acadêmicos e profissionais da saúde apresentam deficit no conhecimento sobre mecanismos fisiopatológicos, avaliação e tratamento da dor [1][2][3] . Esses achados podem refletir os resultados negativos de estudos que apontaram que a dor, seja ela aguda ou crônica, é subdiagnosticada, mal avaliada, subtratada, com baixa resolutividade e por vezes negligenciada em vários níveis de atenção à saúde [4][5][6] .…”
Section: Introductionunclassified